2011
DOI: 10.1097/opx.0b013e3182186bc4
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity with Astigmatic Blur

Abstract: Small levels of crossed cylinder blur (≤0.75 D) produces losses in visual acuity that are dependent on the cylinder axis. Crossed cylinders of 0.75 D produce losses in visual acuity that are twice those produced by defocus of the same blur strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 7 publications
4
51
0
1
Order By: Relevance
“…Similar results were found by Atchison et al 37 and Applegate et al 38 However, for small levels of crossed cylinder blur (≤0.75 DC), it was previously found 8 that astigmatism affects visual acuity more than defocus. Thus the difference between our results and the obtained in that study can be attributed to the different range of blur considered in both cases.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar results were found by Atchison et al 37 and Applegate et al 38 However, for small levels of crossed cylinder blur (≤0.75 DC), it was previously found 8 that astigmatism affects visual acuity more than defocus. Thus the difference between our results and the obtained in that study can be attributed to the different range of blur considered in both cases.…”
Section: Discussionsupporting
confidence: 88%
“…In this sense, a number of studies have not found a strong effect of induced cylinder axis on the changes in VA with astigmatism 19, 20, 21, 22, 23, 30. However, other studies have reported that ATR induced a greater reduction in VA compared to with WTR astigmatism6, 8, 24, 25, 26, 27, 28 and vice versa 25 . Methodological differences in terms of how astigmatism was simulated (with a cross-cylinder, pure positive cylindres, etc.)…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations